STUDY OF PANCHVALKAL KASAYA IN VAGINAL DISCHARGE W.S.R TO ANTIMICROBIAL PROPERTIES (International Journal of Ayurveda and Pharma Research, 2018)
Vaginal Discharge is a common complaint of women coming for medical consultation, it is characterized by discharge per vagina, with itching. It is very common in developing countries like India where unhygienic condition are prevalent, Stressful Modern life styles, Food Habits, Social status. It is common problem which affect women during reproductive age. WHO has estimated that there are 333 million new cases of curable Vulvovaginal infections per year. Many formulations have been mentioned in Ayurvedic texts for treatment of Yonigatasrava. Panchvalkal has been explained in Bhavprakash. The main objective of this review article is to discuss the thereupatic uses of Panchvalkal in various diseases and to discuss the different pharmacological properties and thereupatic uses of Panchvalkal. The selected drug is found to be effective in vaginal discharge w.s.r. to its Antimicrobial properties. It helps in eliminating symptoms like Srava, Kandu, Dorgandhya, Vedana etc. it has Kashya and Katu Properties. These Gunas are effective on vitiated Kapha and normalize it. The present attempt to encompass the up to date comprehensive literature to Study the mode of action of Panchvalkal in vaginal discharge w.s.r. to Ayurvedic properties and Modern pharmacology.